Poland: Social Law and Social Security— Disproportionality to Demographic Challenges - Barański, Michał (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
Social law exists in Poland as an area of research and didactics. However, it is questionable whether social law constitutes a separate scientific discipline (this is the case in Germany, for example). It is partly caused in Poland by the lack of a legal definition of social law. However, it does not change the fact that Poland is currently facing the massive challenge of mastering the demographic crisis and limiting its adverse effects, which requires undertaking deep systemic reforms, especially in such areas as healthcare, social assistance, employment policy, social insurance, and family policy. The most critical factors contributing to demographic ageing in Poland are falling fertility rates and increasing life expectancy. Moreover, the ageing of the post-war baby boomers contributes to demographic ageing in Poland. It is also worth signalling the low labour force participation of older age groups, which consequently means that the actual number of pensioners in Poland is higher than the demographic situation would indicate. All these phenomena undoubtedly pose a challenge to Poland’s social security and healthcare systems. The point of reference for the noted considerations was the European Social Charter, which Poland acceded to in 1997 (Poland was bound by the provisions of all 19 articles of the second part of the Charter, but excluding some paragraphs of these articles). This study first shows the status of the regulation of social rights at the level of the 1997 Polish Constitution. Considering the jurisprudence of the Constitutional Tribunal, the following are described: 1) the right to healthcare and the citizen’s right to equal access to publicly funded healthcare services, 2) the right to social security, 3) assistance to persons with disabilities, 4) the family’s right to assistance from the state, and 5) the protection of children’s rights. Next, the study presents the place of social rights regulations in the Polish legal system. Then, focusing on Poland’s realisation of the right to social security under the European Social Charter, it presents the conclusions of the European Committee of Social Rights from the reporting cycles to date, starting from 1997. Finally, the study details current regulatory issues in the field of social law, showing the problems of sustainable development in light of the aforementioned demographic challenges.KEYWORDS: Poland, social law, social security, European Social Charter, demographic challenges